2014
DOI: 10.1142/e040
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to Spectral Theory and Inverse Problem on Asymptotically Hyperbolic Manifolds

Abstract: Since −∆e ix·ξ = |ξ| 2 e ix·ξ , e ix·ξ is an eigenfunction of −∆. Therefore (0.1) and (0.2) illustrate the expansion of arbitrary functions in terms of eigenfunctions (more appropriately generalized eigenfunctions since they do not belong to L 2 (R n )) of the Laplacian.There are two directions of development of the above fact. One is quantum mechanics, where the Schrödinger operator H = −∆ + V (x) is the most basic tool to decribe the physical system of atoms or molecules. If H has the continuous spectrum, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
73
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(78 citation statements)
references
References 100 publications
5
73
0
Order By: Relevance
“…In [42], it is shown that the asymptotics of the metric of an AHM are uniquely determined (up to isometries) by the scattering matrix S g (λ) at a fixed energy λ off a discrete subset of R. In [65], it is proved that the metric of an AHM is uniquely determined (up to isometries) by the scattering matrix S g (λ) for every λ ∈ R off an exceptional subset. Similar results are obtained recently in [40] for even more general classes of AHM. In [35], it is proved that, for connected conformally compact Einstein manifolds of even dimension n + 1, the scattering matrix at energy n on an open subset of its conformal boundary determines the manifold up to isometries.…”
Section: Scattering Operator and Statement Of The Main Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…In [42], it is shown that the asymptotics of the metric of an AHM are uniquely determined (up to isometries) by the scattering matrix S g (λ) at a fixed energy λ off a discrete subset of R. In [65], it is proved that the metric of an AHM is uniquely determined (up to isometries) by the scattering matrix S g (λ) for every λ ∈ R off an exceptional subset. Similar results are obtained recently in [40] for even more general classes of AHM. In [35], it is proved that, for connected conformally compact Einstein manifolds of even dimension n + 1, the scattering matrix at energy n on an open subset of its conformal boundary determines the manifold up to isometries.…”
Section: Scattering Operator and Statement Of The Main Resultssupporting
confidence: 91%
“…We recall that inverse scattering problems at fixed energy on asymptotically hyperbolic manifolds are closely related to the anisotropic Calderón problem on compact riemannian manifolds with boundary. We refer to the surveys [38,40,46,48,66,71] for the current state of the art on this question. One of the aim of this paper is thus to give examples of manifolds on which we can solve the inverse scattering problem at fixed energy but do not have one of the particular structures for which the uniqueness for the anisotropic Calderón problem on compact manifolds with boundary is known.…”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Liouville surfaces S we are considering in this paper thus possess two asymptotically hyperbolic ends at {x = 0} and {x = A} as well as this remarkable property of separability for the wave equation mentioned above. We refer to [3,11,12,13] for a detailed presentation of general asymptotically hyperbolic surfaces (and higher dimensional asymptotically hyperbolic manifolds) with no hypothesis of (hidden) symmetries or integrability of the geodesic flow. We start defining the main object from which we shall study some inverse problems at fixed energy for such asymptotically hyperbolic Liouville surfaces.…”
Section: Introduction Statement Of the Main Resultsmentioning
confidence: 99%